PKM Validator Desain Rumah Terapung Suku Anak dalam Karya Siswa MAN Insan Cendekia Jambi - Muhammar Khamdevi (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2019)
The settlement of the Anak Dalam tribe in Muara Medak - Jambi often experiences flood disasters later in each rainy season. This is the number of hills that have changed from forests to become oil palm plantations which are unable to absorb water. So that in the rainy season, this area which is a shallow swamp often gets runoff from the hills which causes flooding. MAN Insan Cendikia students try to find a home design solution for residents of the Anak Dalam Tribe at Muara Medak through R & D research with the topic: "Mahaban" Alternative Floating Houses in Handling Floods and Building for Tribal Children in the Village of Muaro Medak Jambi. The results of this study were then included in the Youth Scientific Writing competition (LKIR) organized by the Regional Research and Development Agency (Balitbangda) Jambi. To validate the design, the authors help provide assistance and consultation regarding their designs. This research uses a mix-method. After validation, the design needs to be revised. Then the results were made into a prototype and tested. As a result, this design won the Best Journal Award II and the Second Champion Award at the presentation of the work.